The contribution of teacher, parental and peer support in self-reported school and general well-being among ethnic-cultural minority and majority youth - Valcke, Barbara; Dierckx, Kim; Desouter, Laura; Van Dongen, Stefan; Van Hal, Guido; Van Hiel, Alain (Frontiers in Psychology, 2022)
Social support has been shown to be a crucial element in the well-being of children and adolescents. The present research article investigated how various sources of social support (i.e., parental support, teacher support and peer support) are related to school well-being and general well-being,. A survey was administered to N = 12,215 primary school pupils, pertaining to three ethnic-cultural groups, i.e., the national majority group, the Eastern European minority group and the Middle Eastern minority group. The results showed that perceived teacher support was most strongly and positively related to school well-being, although peer support was also an important determinant of school well-being. All three sources of perceived support were positively related to general well-being. Furthermore, and contrary to previous research, no significant differences were found between both minority groups and the national majority in terms of perceived teacher support. Conversely, both minority groups reported lower perceived parental and peer support. It was further shown that minority status moderated the relationship between the various sources of support and school well-being, although it should be articulated that these effects sizes were fairly small. School diversity, finally, did not yield any relevant effects. Similarities and differences with the existing literature on school well-being are delineated, and potential explanations for these divergences are discussed.